Monitoreo del crecimiento mensual de largo de mecha en ovinos Texel: información preliminar para el desarrollo de un indicador del bienestar animal en la provincia de La Pampa (Veterinary Science, 2025)
This study focuses on the assessment of monthly sheep wool growth, as a preliminary step to using wool cortisol concentration as a stress indicator. This method, adapted from human techniques, can provide a retrospective record of stressful events in animals, promoting animal welfare practices in sheep production. The research involved 46 Texel sheep, individually identified with electronic tags and tattoos, located in the province of La Pampa. For eight months, wool growth was recorded using a Pie Rtw stainless steel ruler and an electronic tag reader for animal identification. The data collected show an average growth of 1.21 cm per month, with variability attributed to individual and environmental factors. Data analysis, based on a regression model, indicated a significant fit with an R² value of 81%, confirming the consistency of the linear model. Preliminary results suggest that regular measurements of wool growth can be used to monitor animal welfare. The correlation between fibre growth and potential stressful events provides a basis for future research looking to implement wool cortisol measurement as a biomarker of stress in sheep. This approach not only has significant implications for animal welfare, but also supports sustainable practices in wool production, aligning with increasing consumer demands for ethical and high-quality products